Clinical outcomes of children and adolescents with sickle cell disease and COVID-19 infection: A year in review at a metropolitan tertiary pediatric hospital - Martin, Olufunke Y.; Darbari, Deepika S.; Margulies, Stefanie; Nickel, Robert S.; Leonard, Alexis; Speller-Brown, Barbara; Martin, Brenda; Barber, John R.; Webb, Jennifer; Majumdar, Suvankar; Sharron, Matthew P.; Campbell, Andrew D. (Frontiers in Medicine, 2023)
Background COVID-19 was declared a global pandemic in March 2020. Early reports were primarily in adults, and sickle cell disease (SCD) was classified as a risk factor for severe COVID-19 disease. However, there are a limited number of primarily multi-center studies reporting on the clinical course of pediatric patients with SCD and COVID-19. Methods We conducted an observational study of all patients with SCD diagnosed with COVID-19 at our institution between March 31, 2020, and February 12, 2021. Demographic and clinical characteristics of this group were collected by retrospective chart review. Results A total of 55 patients were studied, including 38 children and 17 adolescents. Demographics, acute COVID-19 clinical presentation, respiratory support, laboratory findings, healthcare utilization, and SCD modifying therapies were comparable between the children and adolescents. Seventy-three percent (N = 40) of all patients required emergency department care or hospitalization. While 47% (N = 26) were hospitalized, only 5% (N = 3) of all patients required intensive care unit admission. Patients frequently had concurrent vaso-occlusive pain crisis (VOC) (N = 17, 43%) and acute chest syndrome (ACS) (N = 14, 35%). Those with ACS or an oxygen requirement had significantly higher white blood cell count, lower nadir hemoglobin, and higher D-dimers, supporting a pro-inflammatory and coagulopathic picture. Non-hospitalized patients were more likely to be on hydroxyurea than hospitalized patients (79 vs. 50%, p = 0.023). Conclusion Children and adolescent patients with SCD and acute COVID-19 often present with ACS and VOC pain requiring hospital-level care. Hydroxyurea treatment appears to be protective. We observed no mortality despite variable morbidity.